Design, Fabrication, and Test of a Cryogenic Liquid Oxygen-Ethanol Engine - Hojat Ghasemi; Seyed Mohammadreza Mahmoudian; Noordin Qadiri Massoom; S. Rashad Rouholamini; Pouria Mikaniki; Asghar Azimi (فصلنامه علوم و فناوری فضایی, 2022)
The aim of the present research is to obtain the ability to use the cryogenic propellant engines on a laboratory scale. In this regard, it is necessary to build some experimental motors and investigate the their performance parameters. The liquid oxygen as a common oxidizer and ethanol as a green fuel have been selected as propellant components. The engine is designed to produce 400 kgf force at the nominal condition. The pintle type injector has been chosen in which liquid oxygen and fuel are flowed in the axial and radial directions, respectively. The combustion chamber has been protected against overheating by applying the regenerative cooling. However, the laboratory feature of the engine design has provided the using of water instead the cooling propellant. All main components of the engine such as injector, igniter, and flow controllers, are examined by the cold tests. A comprehensive test facility is designed and set up for hot fire tests in which the performance of almost all parameters can be evaluated. Fifteen fire tests have been performed. Maximum obtained pressure and evaluated combustion efficiency were about 75% of design values.